The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1111/j.1095-8649.2000.tb02116.x
|View full text |Cite
|
Sign up to set email alerts
|

Bay‐scale population structure in coastal Atlantic cod in Labrador and Newfoundland, Canada

Abstract: Polymorphisms at five microsatellite DNA loci provide evidence that Atlantic cod Gadus morhua inhabiting Gilbert Bay, Labrador are genetically distinguishable from offshore cod on the north-east Newfoundland shelf and from inshore cod in Trinity Bay, Newfoundland. Antifreeze activity in the blood suggests that Gilbert Bay cod overwinter within the Bay. Gilbert Bay cod are also smaller (weight and length) for their age and consequently less fecund for their age, than cod elsewhere within the northern cod comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(74 citation statements)
references
References 46 publications
6
66
2
Order By: Relevance
“…This phenomenon has also been reported recently for cod in Canadian waters (Robichaud & Rose 2001). Genetically distinct sub-populations in bays, inlets and fjords have been identified in Canada (Ruzzante et al 1996a(Ruzzante et al , 1997(Ruzzante et al , 2000 and Iceland (Jonsdottir et al 2002), and among local spawning populations in the North Sea (Hutchinson et al 2001). Tag-release-recapture experiments have shown that the juvenile and adult coastal cod in Norwegian waters tend to remain in their local areas (Salvanes & Ulltang 1992, Jakobsen 1987, Nordeide & Pettersen 1998, Svåsand et al 2000.…”
Section: Local Retention Of Early Life Stagessupporting
confidence: 77%
“…This phenomenon has also been reported recently for cod in Canadian waters (Robichaud & Rose 2001). Genetically distinct sub-populations in bays, inlets and fjords have been identified in Canada (Ruzzante et al 1996a(Ruzzante et al , 1997(Ruzzante et al , 2000 and Iceland (Jonsdottir et al 2002), and among local spawning populations in the North Sea (Hutchinson et al 2001). Tag-release-recapture experiments have shown that the juvenile and adult coastal cod in Norwegian waters tend to remain in their local areas (Salvanes & Ulltang 1992, Jakobsen 1987, Nordeide & Pettersen 1998, Svåsand et al 2000.…”
Section: Local Retention Of Early Life Stagessupporting
confidence: 77%
“…The year-round residency of the Gadus morhua population in Gilbert Bay is well documented (Ruzzante et al, 2000;Green & Wroblewski, 2000;Morris & Green, 2002). We collected both juvenile and adult G. morhua, as would be expected for a self-sustaining, local population (Wroblewski et al, 2005).…”
Section: Gilbert Bay Resident Speciesmentioning
confidence: 99%
“…These cod have a reddish or golden-brown colour due to their carotenoid-rich diet of invertebrates (Gosse & Wroblewski, 2004;Wroblewski et al, 2005). The Gilbert Bay cod population is genetically distinguishable from coastal cod of eastern Newfoundland and from offshore cod of the Grand Banks (Ruzzante et al, 2000;Beachem et al, 2002). Gilbert Bay cod are a subpopulation of the northern cod metapopulation (Smedbol & Wroblewski, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Part of the difficulty is that different signals seem to emanate from the various genetic systems used. There is an apparent disagreement among workers about the utility of the various molecular markers for population studies (eg, Frydenberg et al, 1965;Jamieson and Jones, 1967;Mork et al, 1985;Carr et al, 1995;Á rnason et al, 2000;Ruzzante et al, 2000;Jó nsdó ttir et al, 2002).…”
Section: Introductionmentioning
confidence: 99%